Civil Society Response to Presidential Election in Social Media Twitter #Pilpres2024 - Sanny Nofrima; Isabella Isabella (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2022)
Abstract:Civil society creates opportunities for prosperity and the realization of the rights of individuals and citizens while naturally creating tools to limit the power and regulate public authorities' activities. The origin of civil society is reflected in the history of the development of civilization which can be described as the desire of thinkers of every age to create an ideal social system in which there is intelligence and justice. The creation of such a society is always associated with the improvement of the rule of law. Civil society involvement activities have the right to be involved in all aspects of political governance and the authority to make decisions and take actions that affect all levels of public life without any institutions in the interests of groups and individuals, and the legitimacy of community-based civil authorities through a political governance system to increase capacity citizens who exercise sovereignty over policies that have a positive impact. The presidential election is a democratic party that is always held every five years; this celebration is the moment civil society has been waiting for. This study aims to determine how civil society responds to the #pilpres2024 by using qualitative methods to find models using social media as mass communication. Data was collected from Twitter social media and analyzed using the Nvivo 12 Plus Application. The results of this study reveal that the effectiveness of using Twitter in disseminating information on #pilpres2024 has proven to be efficient, which succeeded in creating a direct response (observable or encouraging action).AbstrakMasyarakat sipil menciptakan peluang untuk kemakmuran dan realisasi hak individu dan warga negara, sementara secara alami menciptakan alat untuk membatasi kekuasaan dan mengatur aktivitas otoritas publik. Asal usul masyarakat madani tercermin dalam sejarah perkembangan peradaban yang dapat digambarkan sebagai keinginan para pemikir setiap zaman untuk menciptakan sistem sosial yang ideal yang di dalamnya terdapat kecerdasan, kebebasan, kemakmuran, dan keadilan. Terciptanya masyarakat seperti itu selalu dikaitkan dengan perbaikan penegakan supremasi hukum. Aktivitas keterlibatan civil society memiliki hak untuk terlibat dalam semua aspek pemerintahan politik dan otoritas untuk membuat keputusan dan melakukan tindakan yang mempengaruhi semua tingkat kehidupan publik tanpa ada institusi dalam kepentingan kelompok dan individu, dengan kehadiran dan legistimasi otoritas sipil berbasis komunitas melalui sistem pemerintahan politik meningkatkan kemampuan warga negara yang menjalankan kedaulatan atas kebijakan yang berdampak positif. Pemilihan Presiden merupakan pesta demokrasi yang selalu di adakan setiap lima tahun sekali, kemeriahan ini menjadi momen yang tunggu oleh masyarakat sipil. Penelitian ini bertujuan untuk mengetahui bagaimana respon civil society terhadap #pilpres2024 dengan menggunakan metode kualitatif untuk menemukan model dalam penggunaan media sosial sebagai komunikasi massa. Data dikumpulkan dari media sosial Twitter yang dianalisa menggunakan Aplikasi Nvivo 12 Plus. Hasil penelitian ini mengungkapkan bahwa efektivitas penggunaan Twitter pada penyebaran informasi #pilpres2024 terbukti efisien, dimana berhasil menciptakan respon eksplisit (dapat diamati atau mendorong tindakan).